Ovarian follicular development, estradiol and progesterone profile during different days of early pregnancy in buffaloes * - SARATH, T; SINGH, S K; AGARWAL, S K; ARUNMOZHI, N; SAXENA, A (The Indian Journal of Animal Sciences, 2015)
Improvement of reproductive performance of buffaloes requires a better understanding of the mechanisms controlling ovarian follicular growth and development. To study the follicular dynamics and ovarian steroid profile during early pregnancy, 6 buffaloes were selected on the basis of non return rate after insemination and subjected for ultrasonography to confirm the pregnancy as well as follicular development. The mean number of medium, large and total follicles was significantly lower on days 30, 40, 50 and 60 than day 20 of pregnancy indicating reduction in the follicular population with the advancement of pregnancy. There was no significant difference in the diameter of small and medium follicles on different days of pregnancy, however, large follicle significantly decreased with advancement of pregnancy. The progesterone levels fluctuated between 2.52±0.26 and 3.12±0.44 ng/ml until third month of pregnancy. The mean serum estradiol was significantly higher on day 0 and reduced into basal level on first and second month and remained low throughout the study period. In conclusion, on day 20 to 60 of pregnancy, the follicular development is continuous and the number and diameter of larger follicle is decreased as pregnancy advances in buffaloes.